Mathematical Conceptual Understanding of Grade VIII Students Through Discovery Learning Assisted by eXeLearning - Annisa Ummul Khairi; Maulani Meutia Rani; Ahmad Fauzan (Southeast Asian Mathematics Education Journal, 2026)
Students’ mathematical conceptual understanding is a fundamental component in learning mathematics. It plays a crucial role in solving problems and developing higher-order thinking skills. However, previous studies and preliminary observations indicate that students still experience significant difficulties in understanding and applying mathematical concepts effectively. Therefore, innovative instructional approaches are needed to address this issue. This study aims to examine the development of students’ mathematical conceptual understanding and to determine its significance among students taught through a Discovery Learning model assisted by eXeLearning, compared to a conventional learning approach. A descriptive and quasi-experimental design was employed by using a Non-Equivalent Post-test Only Control Group Design. The population consisted of nine eighth-grade classes at one public junior high school in a city, from which two classes were selected through simple random sampling: Class VIII.1 as the experimental group and Class VIII.3 as the control group. The research instruments included essay-based quizzes and a post-test measuring students’ mathematical conceptual understanding. The quiz results showed a gradual increase in students’ conceptual understanding across learning sessions. Post-test data were analysed using an independent samples t-test. The results of the independent samples t-test indicated that students who learned using Discovery Learning assisted by eXeLearning achieved significantly higher mathematical conceptual understanding than students who learned through conventional instruction. These findings suggest that integrating Discovery Learning with digital learning media such as eXeLearning can effectively support students in constructing and strengthening their mathematical conceptual understanding.